2019
DOI: 10.3762/bxiv.2019.70.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An improved, scalable synthesis of Notum inhibitor LP-922056 using 1-chloro-1,2-benziodoxol-3-one as a superior electrophilic chlorinating agent

Abstract: Background: The carboxylesterase Notum has been shown to act as a key negative regulator of the Wnt signalling pathway by mediating the depalmitoleoylation of Wnt proteins. LP-922056 (1) is an orally active inhibitor of Notum. We are investigating the role of Notum in modulating Wnt signalling in the central nervous system and wished to establish if 1 would serve as a peripherally restricted control. An accessible and improved synthetic route would allow 1 to become more readily available as a chemical tool to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…7,13 Although 1 demonstrates good oral bioavailability, additional pharmacokinetic studies in mouse showed negligible brain exposure. 20 Scaffold-hopping from acid 1 identified amide 2 as a potent inhibitor of Notum. 14 Pharmacokinetic studies in mouse with oral administration of 2 showed improved brain penetration with a brain:plasma concentration ratio of 0.29.…”
Section: Introductionmentioning
confidence: 99%
“…7,13 Although 1 demonstrates good oral bioavailability, additional pharmacokinetic studies in mouse showed negligible brain exposure. 20 Scaffold-hopping from acid 1 identified amide 2 as a potent inhibitor of Notum. 14 Pharmacokinetic studies in mouse with oral administration of 2 showed improved brain penetration with a brain:plasma concentration ratio of 0.29.…”
Section: Introductionmentioning
confidence: 99%
“…That being, it is not either cyclic or bridged in nature such as Togni's range of reagents, 35 or presents as ionic in nature for the chloride such as the [PhICF3][Cl] iodonium salt (scheme 10). 36 Cyclic λ 3 -chloroiodanes do not present with enhanced chlorinating activity comparative to the asymmetric species analogous to I5, are typically described as mild, 37 and their general application is to access Togni's range of trifluoromethylation reagents rather than for chlorination. 38 Scheme 10.…”
Section: Aricl(otf)mentioning
confidence: 99%
“…Fish and co‐workers have used a heterocyclic chlorination in their synthesis of the Notum inhibitor LP‐922056 ( 128 , Scheme 51). [71] The carboxylesterase Notum is involved in the Wnt signaling pathway, whose dysregulation is linked to Alzheimer ’s disease.…”
Section: Applications Of Chloroiodanesmentioning
confidence: 99%